Validity and Practicality of PBL-SSI E-Module on Ecology and Biodiversity Topic for Junior High School - Nispu Rahma, Septina; Oktavia, Rani; Yurnetti (SEMESTA: Journal of Science Education and Teaching, 2025)
Teaching materials, as one of the essential components in the learning process, must evolve in line with rapid technological advancements. Therefore, E-module teaching materials need to be developed to enhance students’ understanding and learning outcomes. This study employed Research and Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate) to develop a Problem-Based Learning (PBL)-based E-module integrated with Socio-Scientific Issues (SSI) on ecology and biodiversity topics for junior high school students. The research instruments included teacher interview sheets, student needs analysis questionnaires, validity questionnaires, and practicality questionnaires. Data were analyzed for validity and practicality. The findings revealed that the developed PBL-based E-module integrated with SSI achieved a very valid category, with an average validity score of 90%, and a very practical category, with an average practicality score of 96%. It can be concluded that the PBL-based science learning E-module integrated with SSI on ecology and biodiversity meets the criteria of validity and practicality, making it suitable for use by teachers and students.